Comparing the Effectiveness of Dialectical Parenting and Mindful Parenting Training on the Parenting Adaptability of Mothers of Primary School Children in Shiraz - Mohebi , Sardar; Torkan , Hajar; Bahramipour Isfahani , Mansoureh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The purpose of the present study was to compare the effectiveness of dialectical parenting training and mindful parenting training on the parenting adaptability of mothers of primary school children in Shiraz. Methods and Materials: The research design was quasi-experimental with a pretest, posttest, and 60-day follow-up with a control group. It was conducted to compare the effectiveness of dialectical parenting training and mindful parenting training on the parenting adaptability of mothers of primary school children. The statistical population included all mothers of 6- to 10-year-old children studying in primary school during the 2025-2026 academic year, who had above-average anxiety scores on the Parenting Anxiety Questionnaire (Ataabadi et al., 2021). The sample of this study was selected using convenience sampling from mothers of 8- to 10-year-old children who exhibited symptoms of parenting anxiety based on the questionnaire. For sampling, after obtaining permission from the university and making necessary coordination with counseling centers, 60 mothers were selected via convenience sampling based on inclusion and exclusion criteria and randomly assigned into two experimental groups and one control group (20 individuals per group). The first experimental group received dialectical parenting training, the second experimental group received mindful parenting training, and the third group received no training. The research instrument was the Adaptability Questionnaire (Yousefi et al., 2011). Data analysis was performed using descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures analysis of variance and Bonferroni post hoc test) using SPSS-26 software. Findings: The results showed that there is no significant difference between the effectiveness of the dialectical parenting intervention and mindful parenting on the adaptability of primary school children in Shiraz (p>.05). Conclusion: Based on the analysis of the findings of the present study, parenting methods can help improve psychological constructs among mothers of primary school children. In this regard, dialectical parenting training and mindful parenting training were equally effective on the aforementioned variables.